MULTISPECTRAL IMAGE FUSION USING SLANTLET-BASED RIDGELET TRANSFORM (Journal of Engineering, 2007)
This paper introduces a new method in the multispectral image fusion based on ridgelettransform which represents edges better than wavelets. Since edges play a fundamental rule inimage understanding, one good way to enhance spatial resolution is to enhance the edges. Ridgeletbased image fusion method provides richer information in the spatial and spectral domainssimultaneously. Also another method introduced based on new Hybrid transform which isimprovement from the Ridgelet transform. Here we used our method to merge the panchromaticimage of IKONOS sensor (1m resolution) with its multispectral image (4m resolution). Thesoftware used in this paper is (Matlab V 7.0.4 ).